Investigation of vocabulary learning strategies and the difficulty faced by the students of junior high school - Rahmi, Aulia; Nirwanto, Rahmadi; Qamariah, Zaitun (Universitas Pahlawan Tuanku Tambusai, 2025)
Vocabulary plays a vital role in language acquisition, especially for students studying English as a Foreign Language (EFL), as it significantly affects their comprehension, communication skills, and academic success. However, students in Islamic junior high schools encounter unique challenges due to their exposure to multiple languages and the integration of religious themes, which are often not addressed in current research. This research aims to investigate the vocabulary learning strategies used by students at MTs Muslimat NU Palangka Raya, along with the challenges they face. A mixed-methods approach was employed, gathering data through questionnaires, interviews, and classroom observations. The results indicate that cognitive and social strategies are the most commonly utilized, while challenges include difficulties with vocabulary retention, pronunciation issues, and language interference. The study concludes that integrating contextually and culturally relevant approaches into vocabulary teaching can improve student learning and retention, especially in religious educational contexts.